Plastic Surgery Chairs and Program Directors: Are the Qualifications Different for Men and Women?. Issue 2 (August 2020) - Zhang, Ben; Chen, Kevin; Ha, Grace; Smith, Mark L.; Bradley, James P.; Thorne, Charles H.; Kasabian, Armen K.; Pusic, Andrea L.; Tanna, Neil
Abstract : Background: The gender disparity between the number of female and male chairs and program directors has been previously established. The aim of this study was to determine whether any differences in objective credentials existed between male and female plastic surgery department chairs/division chiefs and program directors. Methods: Information about each plastic surgery program director and chair/chief was extracted from the websites of all institutions affiliated with a plastic surgery residency program. For each individual, information about the length of their career, number of fellowships completed, and number of publications was recorded. The two-tailed t test was used to compare differences between male and female chairs and program directors. Results: A total of 99 chairs were recorded, of which nine (9.1 percent) were female. Of the 99 program directors, 13 (13.1 percent) were female. There was no difference in the number of years in practice or number of fellowships between men and women for either position. On average, male chairs had significantly fewer publications than female chairs (71.9 versus 128; p < 0.05). There was no significant difference in the number of publications between male and female program directors. Compared to program directors, chairs had significantly more years in practice and numbers of publications, which held true for both men and women. Conclusions: Women are not only underrepresented in the department chair and program director positions, but also possess higher qualifications that may reflect differences in standards for promotion and appointment. Additional research is needed to elucidate the reasons behind the observed differences in qualifications.